2022
DOI: 10.1111/cas.15285
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cα activation switches YAP1 from TEAD‐mediated signaling to p73‐mediated signaling

Abstract: Yes-associated protein 1 (YAP1) was originally discovered as a WW domain-containing SRC kinase-binding protein. 1 YAP1 is distributed in the cytoplasm and in the nucleus. 2 YAP1 interacts with various transcription factors such as the TEAD family proteins, SMAD proteins, RUNX, and p73 to regulate gene transcription in the nucleus, while YAP1 undergoes proteasome degradation in the cytoplasm. [2][3][4][5][6][7] Therefore, cytoplasmic YAP1 is thought to be inactive, while nuclear YAP1 is considered to be active.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This would clearly demonstrate that cytoplasmic YAP1 promoted autophagic death of breast cancer cells. Activation of the Hippo pathway was crucial to regulating the subcellular localization of YAP1; when the Hippo pathway was activated, the downstream classic molecule YAP1 was phosphorylated and could not enter the nucleus, and thus remained in the cytoplasm [ 3 , 10 , 52 , 53 ]. We used NPASS to screen 48 natural small‐molecule compounds related to the breast cancer cell lines MDA‐MB‐231, MDA‐MB‐468, and MCF7 (Supplementary Figure S3A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This would clearly demonstrate that cytoplasmic YAP1 promoted autophagic death of breast cancer cells. Activation of the Hippo pathway was crucial to regulating the subcellular localization of YAP1; when the Hippo pathway was activated, the downstream classic molecule YAP1 was phosphorylated and could not enter the nucleus, and thus remained in the cytoplasm [ 3 , 10 , 52 , 53 ]. We used NPASS to screen 48 natural small‐molecule compounds related to the breast cancer cell lines MDA‐MB‐231, MDA‐MB‐468, and MCF7 (Supplementary Figure S3A ).…”
Section: Resultsmentioning
confidence: 99%
“…The functions of YAP1 in inhibiting cell proliferation and promoting apoptosis were partially attenuated but not completely reversed by CQ and siATG7 , indicating that there may be other mechanisms for YAP1 to inhibit breast cancer. It seems that the inhibition of P73 expression by nuclear YAP1 in the literature may provide a partial explanation [ 9 , 10 ]. The impact of YAP1 on breast cancer fate still needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YAP1 does not contain DNA-binding sequences; thus, the binding partners are important for its function. YAP1 binds to TEADs to facilitate the expression of tumor-promoting genes, and YAP1 may switch to bind to TP73 to promote apoptosis of cancer cells ( 19 ). Therefore, we also analyzed the expression of TEADs and TP73 in pan-cancer.…”
Section: Resultsmentioning
confidence: 99%
“…To date, a direct link between PKC and PML has not yet been reported, but one study showed that PKC activation resulted in PML-mediated SUMOylation of YAP1 [ 35 ], thus indirectly suggesting that there is (at least) an indirect PKC–PML interaction. Interestingly, sc-3088 is a peptide inhibitor corresponding to amino acids 19-31 of the pseudosubstrate domain expressed in the primary structures of the α, βI, βII, and γ isoforms of PKC and is significantly similar to stretches in the pseudosubstrate domains present in all novel and atypical PKC isoforms [ 36 ].…”
Section: Discussionmentioning
confidence: 99%